Polymeric prosthetic heart valves: A review of current technologies and future directions - Singh, Sameer K.; Kachel, Mateusz; Castillero, Estibaliz; Xue, Yingfei; Kalfa, David; Ferrari, Giovanni; George, Isaac (Frontiers in Cardiovascular Medicine, 2023)
Valvular heart disease is an important source of cardiovascular morbidity and mortality. Current prosthetic valve replacement options, such as bioprosthetic and mechanical heart valves are limited by structural valve degeneration requiring reoperation or the need for lifelong anticoagulation. Several new polymer technologies have been developed in recent years in the hope of creating an ideal polymeric heart valve substitute that overcomes these limitations. These compounds and valve devices are in various stages of research and development and have unique strengths and limitations inherent to their properties. This review summarizes the current literature available for the latest polymer heart valve technologies and compares important characteristics necessary for a successful valve replacement therapy, including hydrodynamic performance, thrombogenicity, hemocompatibility, long-term durability, calcification, and transcatheter application. The latter portion of this review summarizes the currently available clinical outcomes data regarding polymeric heart valves and discusses future directions of research.